Biochemical characterization of the Micrurus pyrrhocryptus venom - Dokmetjian, Christian (2009)
Fil: Dokmetjian, Christian. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Producción de Biológicos; Argentina.